Penanganan Sengketa Aset Daerah Melalui Musyawarah Dan Negosiasi - Nur Syahputri, Nivarica Aurel; Azhar, M. Kholidul; Ansori, Ansori (PAMALI: Pattimura Magister Law Review, 2024)
Introduction: Handling disputes over regional assets is an important issue in the management of local government wealth. Regional asset dispute resolution through deliberation and negotiation as an alternative to litigation. Disputes often arise due to unclear asset registration, such as in the case of land disputes between the local government and the community or other parties.Purposes of the Research: This study aims to find out the handling of regional asset disputes carried out through deliberation and negotiation and this research contributes to efforts to improve regional asset management in Indonesia.Methods of the Research: The type of research used is normative juridical research or literature law research method, namely reviewing laws and regulations and relevant case studies on the Handling of Regional Asset Disputes Through Deliberation and Negotiation to be the material for study in finding answers to the legal issues studied.Results of the Research: The results show that while deliberation and negotiation can be an effective solution to avoid time-consuming and costly court proceedings, often the results achieved are not satisfactory to both parties. Therefore, in addition to deliberation and negotiation, a historical approach and accurate administrative and physical recording of regional assets are needed to prevent future disputes.